HASIL BELAJAR BAHASA INGGRIS DAN KETERAMPILAN GURU DALAM MENGAJAR - Ramli Ramli (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2011)
The result of learning is coming from the skill someone has accepted after following learning activities. Students’ achievement can be seen from various domains they are cognitive, affective, psychomotoric. To know the skill that students have to achieve, we need to pay attention toward learning achievement as well as the quality of students’ changed behaviour. This article discusses about 6 teaching skills that teachers should own, namely: (1) skill to open the teaching, (2) skill to explain, (3) skill to question, (4) skill to emphasize, (5) skill to conduct various techniques in teaching learning, and (6) skill to close the teaching learning process.